1999
DOI: 10.1076/ocii.7.1.51.8113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose and long-term oral acyclovir therapy after penetrating keratoplasty for herpes simplex heratitis

Abstract: Our results suggest that postoperative oral acyclovir therapy is effective in preventing the recurrence of herpetic infection. However, the recurrence may develop after cessation of oral acyclovir therapy, especially in patients who underwent PK for corneal perforation due necrotizing HSK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…15 Although evidence on the optimal duration and dosage for antiviral prophylaxis is divided in the literature, long-term prophylactic oral acyclovir significantly decreased the recurrence of herpes simplex keratitis following keratoplasty 16 and reduces corneal graft failure in patients with a history of recurrent herpes simplex keratitis. [17][18][19][20] It is therefore surprising that antiviral prophylaxis was prescribed by fewer than half of the participants in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although evidence on the optimal duration and dosage for antiviral prophylaxis is divided in the literature, long-term prophylactic oral acyclovir significantly decreased the recurrence of herpes simplex keratitis following keratoplasty 16 and reduces corneal graft failure in patients with a history of recurrent herpes simplex keratitis. [17][18][19][20] It is therefore surprising that antiviral prophylaxis was prescribed by fewer than half of the participants in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal transplantation for corneal scarring induced by HSV can restore vision and induce rapid recovery. Recurrence of herpetic keratitis in the transplanted graft, however, may lead to corneal graft rejection and a decrease in vision due to recurrence of HSV in the transplanted cornea [37][38][39][40][41][42]. It is therefore suggested that long-term prophylaxis with topical ganciclovir gel or acyclovir ointment might help to prevent recurrence of the disease and subsequent graft rejection.…”
Section: Corneal Transplantation In Patients With Herpetic Keratitismentioning
confidence: 92%
“…5, 6) [43]. The use of topical antiviral prophylaxis may help in the prevention of recurrence of herpetic keratitis in patients with corneal grafts [38,42]. It appears that prophylaxis in patients who have undergone PKP for herpetic disease is essential in the prevention of corneal graft failure.…”
Section: Corneal Transplantation In Patients With Herpetic Keratitismentioning
confidence: 93%
“…Reaktivasyonun ve AR'nin en sık görüldüğü ve steroidlerin yoğun olarak kullanıldığı PK sonrası ilk yıl antiviral koruma (oral asiklovir 800 mg /gün) uygulanması önerilmektedir. [20][21][22] Bu olguda da PK sonrası ilk 7 ay profilaktik asiklovir kullanılmıştır. Ancak AR tedavisinde çok daha yoğun uygulanan steroidler de HSV reaktivasyonu ihtimalini arttırır.…”
Section: Discussionunclassified